2021
DOI: 10.1007/s10508-020-01901-w
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vision in the Emergence of Mate Preferences

Abstract: Cross-cultural research has repeatedly demonstrated sex differences in the importance of partner characteristics when choosing a mate. Men typically report higher preferences for younger, more physically attractive women, while women typically place more importance on a partner’s status and wealth. As the assessment of such partner characteristics often relies on visual cues, this raises the question whether visual experience is necessary for sex-specific mate preferences to develop. To shed more light onto th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Some participants emphasized the beautiful and expressive voice of their ideal partner as one of their criteria for marriage. Accordingly, the researchers showed that auditory ability is an important mate selection criterion for both men and women with blindness disorders (Scheller et al, 2021; Sorokowska et al, 2018). Another study showed that emotional maturity is an important criterion for marriage for VI youth (Pinquart & Pfeiffer, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some participants emphasized the beautiful and expressive voice of their ideal partner as one of their criteria for marriage. Accordingly, the researchers showed that auditory ability is an important mate selection criterion for both men and women with blindness disorders (Scheller et al, 2021; Sorokowska et al, 2018). Another study showed that emotional maturity is an important criterion for marriage for VI youth (Pinquart & Pfeiffer, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, people with no myopia in our sample also have two options: mate with the person who also has no myopia and mate with the person who has myopia. According to the research, the importance of high status and likable personality was not influenced by sightedness [4]. Since there is no clear preference mate in the United States society between people who have myopia and have not, 50% of people with myopia mate to people also with myopia, and another 50% of people with myopia mate to people with no myopia.…”
Section: Mate Probability In the Samplementioning
confidence: 94%
“…Unlike visual faces, however, tactile faces are not a highly ecologically relevant stimulus, either for sighted or blind people. Although we have experience touching our own face, and perhaps the faces of one or two other people, touch is not typically used to recognize either identity or emotional expressions of other people ( Scheller et al, 2021 ). Sighted people are unlikely to recognize a mask made from their own face when only using touch ( Casey and Newell, 2005 ).…”
Section: Comparing Function Of Domain-specific Votc Regions In Sighte...mentioning
confidence: 99%